Pathos : distúrbio passional e terapia em Epicteto - Luz, Diogo da (2018)
According to Stoicism, passions are soul sufferings that occur due to irrationalities. They happen when one ignores virtue, which is the same as conformation to the natural logos. Therefore, to fight passions it is necessary to properly use reason. In this sense, for Stoic thinkers, the philosophical practice shows itself capable of contributing to psychological well-being, since it aids in eliminating erroneous opinions that provoke passions. In this same way thinks Epictetus, a stoic philosopher who deepened, in his own way, the relationship between the art of philosophy and the art of living. For Epictetus, passions relate more specifically to human desires, unlike the approach of his predecessors that related them generically to impulses.